APLIKASI PENCARIAN RUTE TERPENDEK LOKASI KULINER KHAS PALEMBANG MENGGUNAKAN ALGORITMA EUCLIDEAN DISTANCE DAN A*(STAR) - Dona Marcelina; Evi Yulianti (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Palembang is one of the regions in Indonesia which is known for having culinary which has a distinctive and delicious taste. Besides having a distinctive taste, Palembang cuisine also has its own story related to the history of Palembang City and the development of people's lives there. The many types of culinary and culinary tourist attractions in the city of Palembang provide its own obstacles for tourists and local residents in choosing a culinary meal and the route to the culinary location. The solution to the problem proposed is to make the application for the shortest route search for culinary locations typical of Palembang using the Euclidean Distance and A * algorithm. Euclidean Distance algorithm which is a calculation of the distance from two points as a basis in finding the shortest route and gives the user information about the location that is around the user by comparing the distances and applying the A * algorithm as a basis in finding the shortest route using the smallest estimated cost to achieve the goals to be achieved, and has a heuristic value that is used as a basis for consideration. The final results of the study showed that the algorithm performed had a high degree of accuracy in determining the shortest culinary route location in Palembang, namely the Mean Mean percentage error (MAPE) of 4.4%.